Enhanced Inducible Costimulator Ligand (ICOS-L) Expression on Dendritic Cells in Interleukin-10 Deficiency and Its Impact on T-Cell Subsets in Respiratory Tract Infection - Xiaoling Gao; Lei Zhao; Shuhe Wang; Jie Yang; Xi Yang (BMC, 2013)
Abstract An association between inducible costimulator ligand (ICOS-L) expression and interleukin (IL)-10 production by dendritic cells (DCs) has been commonly found in infectious disease. DCs with higher ICOS-L expression and IL-10 production are reportedly more efficient in inducing regulatory T cells (Tregs). Here we use the Chlamydia muridarum(Cm) lung infection model in IL-10 knockout (KO) mice to test the relationship between IL-10 production and ICOS-L expression by DCs. We examined ICOS-L expression, the development of T-cell subsets, including Treg, Th17 and Th1 cell, in the background of IL-10 deficiency and its relationship with ICOS-L/ICOS signaling after infection. Surprisingly, we found that the IL-10 KO mice exhibited significantly higher ICOS-L expression by DCs. Moreover, IL-10 KO mice showed lower Tregs but higher Th17 and Th1 responses, but only the Th17 response depended on ICOS signaling. Consistently, most of the Th17 cells were ICOS+, whereas most of the Th1 cells were ICOS− in the infected mice. Furthermore, neutralization of IL-17 in IL-10 KO mice significantly exacerbated lung infection. The data suggest that ICOS-L expression on DC may be negatively regulated by IL-10 and that ICOS-L expression on DC in the presence or absence of IL-10 costimulation may promote Treg or Th17 response, without significant impact on Th1.